Young People, Religion, and the Everyday Practice of Popular Culture: The Case of Urban Muslim Young People - Hariyadi Hariyadi (MOZAIK HUMANIORA, 2016)
This article aims to reveal popular culture and religious practices of urban Muslim youth in everyday life. By utilizing interviews, focus group discussions, and participant observation to informants who are students in Jakarta and Bandung, especially the State University of Jakarta and Bandung Institute of Technology, this research showed that they had mixed views on popular culture, religion, and the relationship between them. On the one hand, they assume that the majority of popular culture has a negative impact toward religious practices. Popular culture reduced the time for someone to get closer to God. On the other hand, they cannot detach themselves from popular culture and consume it. In addition, they put religion as something that is not completely dogmatic but can be adjusted with the condition of individual believers, including young people. They can be said to be in the stage of knowing themselves and their religion, thus having the tendency to be more  open in accepting forms of popular culture that are not considered fully in accordance with their religious beliefs. Their consumption of popular culture and declaration of religion suggests that urban young people in Indonesia are aiming to be modern and pious at the same time. In doing so, urban Indonesian Muslim young people demonstrate that they do not exclusively belong to either Westernisation or Islamism; they are creating their own distinctive identity.